Pengaruh Madu Ceiba Pentandra Terhadap Kadar LDL Tikus Rattus Norvegicus Yang Diberi Diet Tinggi Lemak - Hetti Rusmini; Devita Febriani Putri; Hidayat Hidayat; Dhani Risandy (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Hypercholesterolemia is a condition of the body that has increased cholesterol levels above the normal threshold (<200 mg/dL). Hypercholesterolemia can occur because of lifestyle that not healthy, ranging from diet is not balanced to the lack of sporting activity. Hypercholesterolemia is the main risk factor for atherosclerosis which is the increase in Low Density Lipoprotein (LDL). Methodology: The type of research used is purely experimental using a pre and post test design with group design. The population used in this study were 25 male Wistar strain rats which were divided into 5 groups. Sampling using the method of total sampling. Data were analyzed by Paired T-test and Anova. Research Results: In this study, from the 5 sample groups obtained the results of the analysis Paired T-Test, obtained a significant increase (p <0.05) of LDL levels after giving a high-fat diet in the negative group (p = 0.025), treatment group 2 (p = 0.001), and treatment group 3 (p= 0.001). In the treatment after the administration of honey, there was a significant decrease (p <0.05) of LDL levels in 2 groups, namely in the treatment group 2 (p = 0.026), and the treatment group 3 (p = 0.092). With Anova analysis, a significant difference was found in the treatment after the administration of a high-fat diet and after the provision of honey honey with the same p value, namely p = 0.001 (P <0.05). Conclusion: There are differences that influence the administration of honey honey on LDL levels in wistar strain rats given a high-fat diet.